Characterization of the anti-IMPDH2 autoimmune response and biological aspects of the "rods and rings" structures targeted by anti-IMPDH2 autoantibodies - Keppeke, Gerson Dierley [UNIFESP] (2015)
Enzyme aggregation into non-membrane bound large bodies is a common feature among eukaryotic cells. In the last five years, many reports have described the ability of Cytidine Triphosphate Synthase (CTPS) and Inosine Monophosphate Dehydrogenase (IMPDH2), enzymes that are critical in the cytidine and guanine nucleotide biosynthesis pathways, respectively, to form aggregates named rods and rings (RR) or cytoophidia ("cellular snakes"). Interestingly, a considerable fraction of hepatitis C (HCV) patients treated with IFN-alpha plus ribavirin, an inhibitor of IMPDH2, develops autoantibodies against the RR structures. We study aspects of the formation of RR structures in vitro and in vivo, as well as explore the temporal evolution of anti-RR autoantibodies production. By studying the process of aggregation of IMPDH2 and CTPS into RR structures in the presence of their respective inhibitors, we demonstrated the independent in vitro formation of IMPDH2-based and CTPS-based RR structures in cell lines of two mammalian species, and reported that both enzymes can interact in the formation of mixed RR structures as a mosaic of IMPDH2 and CTPS aggregates. By studying the temporal behavior of RR IMPDH2-based structures in living cells in vitro, we show the disassembly of RR structures in the presence of an antibody targeting IMPDH2, a molecular constituent of RR. We also demonstrate that the IMPDH2-inhibitory drugs ribavirin and MPA generate IMPDH2-rich RR structures in vivo in PBMC from HCV and SLE patients, respectively, but only ribavirin-treated HCV patients present anti-RR autoantibodies. The autoantibodies that elicit the anti-RR indirect immunofluorescence pattern recognized predominantly the IMPDH2 enzyme. By analyzing the temporal behavior of the anti-RR/IMPDH2 autoimmune response, we report that such autoantibodies were induced at 3 to 6 months of IFN-alpha+ribavirin treatment, reached a plateau around the twelfth month, and decreased/disappeared after treatment conclusion. The above described scenario characterizes a human model of immune tolerance breakdown and represents a unique opportunity to study various aspects of the autoimmune response development in humans.